Eleonora Ziemięcka, the First Polish Woman Philosopher: On the Essence and the Role of Philosophical Thinking - Usakiewicz, Joanna (Studia z Historii Filozofii, 2021)
Eleonora Ziemięcka (1815-1869) is considered the first Polish woman philosopher. She represented Christian philosophy. She expressed her philosophical views most profoundly in a work Zarysy filozofii katolickiej w czterech poglądach zawarte [Outlines of Catholic Philosophy Included in Four Views]. She also spoke about the education of women, to which she devoted the work Myśli o wychowaniu kobiet [Thoughts on Education of Women]. In the text Myśli o filozofii [Thoughts on Philosophy], published in 1840, she presented her thoughts on the essence and role of philosophy. It is this issue that is discussed in this article.